An Analysis of Code-switching and Code-mixing in Indah G and Andovi Da Lopez’s “Indah G Show on YouTube” - Luthfiatunnisa; Dzakiah; Zulfikri (Indonesian Journal Publisher, 2025)
This study investigates the forms and functions of code-switching and code-mixing in a bilingual podcast episode of The Indah G Show on YouTube, featuring Indah Gunawan and Andovi Da Lopez. Using a qualitative research design, discourse analysis was applied to examine 132 instances of code-switching and 187 of code-mixing. Poplack’s (1980) and Muysken’s (2000) typologies were used to classify structural forms, while Hoffman’s (1991) framework was employed to identify their communicative functions. The analysis revealed that intra-sentential switching and insertion were the most frequently used types, indicating a high degree of bilingual fluency and integration. The most dominant function was clarifying speech for the listener, followed by discussing specific topics and expressing group identity. These findings demonstrate that language alternation in digital media is both strategic and context-sensitive, allowing bilingual speakers to engage audiences, convey meaning more effectively, and construct fluid linguistic identities. The study offers empirical insights into bilingual language use in online entertainment and contributes to a broader understanding of multilingual practices in digital communication